The resiliency of the Philippine Banking Industry during the 2008 financial and economic crisis. - Morales, Michelle Risa Cata-al
This study aims to discuss and analyze the performance of the top five universal banks in the Philippines from the year 1998 to 2010. The selected performance indicators used in analyzing individual bank performances are total assets, total capital, non-performing loans (NPLs) and return on equity (ROE). Furthermore, this study seeks to identify and assess, in terms of their effectiveness in sustaining banking performance, the various strategies imposed and/ or adopted by the top five universal banks in the country as a response to the recent crisis. The strategies imposed and adopted to sustain and improve banking performance were also included. In line with the objectives of this study, the descriptive analysis method was used. Results indicated that the top five banks in country maintained their strong performance amidst the 2008 financial and economic crisis. The focus of the banks' strategies was mainly on risk management and the strengthening of their respective balance sheets. Strategies implemented by the banks proved to be effective and thus made them resilient to the crisis. Policy implications and recommendations are discussed at the end of the study.